2020
DOI: 10.1530/eje-20-0656
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hyperaldosteronism subtypes when adrenal vein sampling is unilaterally successful

Abstract: Objective – Adrenal venous sampling (AVS) is the gold standard to discriminate patients with unilateral primary aldosteronism (UPA) from bilateral disease (BPA). AVS is technically-demanding and in cases of unsuccessful cannulation of adrenal veins, the results may not be interpreted. The aim of our study was to develop diagnostic models to distinguish UPA from BPA, in cases of unilateral successful AVS and the presence of contralateral suppression of aldosterone secretion. Design – Retrospective evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Without a bilaterally selective procedure, the LI, which is the most widely accepted index in the literature, is not applicable to guide the diagnosis of lateralization of aldosterone hypersecretion and the subsequent opportunity of surgical treatment. Therefore, the introduction of unconventional indices and statistical models ( 25 27 , 37 , 38 ) could help in determining the lateralization of aldosterone secretion in case of suboptimal AVS. Our group recently demonstrated the high accuracy of corrected unconventional indices in the prediction of unilateral disease in a large series of patients with PA subtyped with AVS ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without a bilaterally selective procedure, the LI, which is the most widely accepted index in the literature, is not applicable to guide the diagnosis of lateralization of aldosterone hypersecretion and the subsequent opportunity of surgical treatment. Therefore, the introduction of unconventional indices and statistical models ( 25 27 , 37 , 38 ) could help in determining the lateralization of aldosterone secretion in case of suboptimal AVS. Our group recently demonstrated the high accuracy of corrected unconventional indices in the prediction of unilateral disease in a large series of patients with PA subtyped with AVS ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during last years, some authors proposed the use of simple unconventional indices with a moderate (19,20), and often not reproducible, accuracy for determining PA lateralization (21)(22)(23)(24). Most recently, Burrello et al developed two scores (25,26) for predicting PA subtypes, using a machine learning approach and reaching a high accuracy; similarly, our group proposed the use of adjusted unconventional AVS indices in order to determine the lateralization of aldosterone secretion when adrenal vein cannulation is not bilaterally selective (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find an optimal prediction model, five supervised machine learning classifiers were used, including random forest (RF), support vector machines (SVM), gradient boosting decision tree (GBDT), logistic regression (LR), and AdaBoost. First, all possible available variables were used to build models, according to previous research reports ( 7 , 10 , 11 ). Two parameters, urinary PAC and PRA after the furosemide standing test, were removed due to their low importance for the prediction model, relatively poor availability, and absence from the external validation dataset.…”
Section: Methodsmentioning
confidence: 99%
“…This clinical score can be used to subtype primary aldosteronism when adrenal vein sampling is unavailable or fails. Another study suggested a clinical prediction score to subtype primary aldosteronism when adrenal vein sampling is only unilaterally successful [16]. The contralateral ratio (ratio of aldosterone/cortisol in the contralateral adrenal vein to that in the peripheral vein), in addition to aldosterone levels, potassium levels, and CT imaging, showed a high diagnostic value, with an area under the receiver operating characteristic curve of 0.971.…”
Section: Scoring System For Subtyping Primary Aldosteronismmentioning
confidence: 99%